2008
DOI: 10.1002/ajim.20613
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy, comprehensibility, and use of material safety data sheets: A review

Abstract: Despite the fact that these studies varied in methodology and spanned a period of more than 15 years, a number of common themes emerged regarding inaccuracies, incompleteness, incomprehensibility and overall low use of MSDSs. The results of the literature review suggest that there are serious problems with the use of MSDSs as hazard communication tools. The article concludes with recommendations for governments, regulatory bodies, and occupational health and safety personnel to seriously reassess the ways in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 39 publications
(127 reference statements)
3
22
0
Order By: Relevance
“…The habit of describing generic RMMs in the SDS is a contributing factor to a major part of the complaints about SDSs, which connect to previous findings of previous studies of SDSs (e.g. Nicol et al, 2008). The findings of the present study show that the issues with SDSs and supply chain communication are far from resolved by the current state of implementation of REACH.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The habit of describing generic RMMs in the SDS is a contributing factor to a major part of the complaints about SDSs, which connect to previous findings of previous studies of SDSs (e.g. Nicol et al, 2008). The findings of the present study show that the issues with SDSs and supply chain communication are far from resolved by the current state of implementation of REACH.…”
Section: Discussionsupporting
confidence: 55%
“…Shortcomings of the SDS have been found in numerous studies over the years, both in European countries and others; for instance that SDS are not made available to workers, are not fully accurate and/or complete and contain insufficient information to allow identification of all hazards or sufficient RMMs (Nicol et al, 2008;Suleiman and Svendsen, 2014). The SDS improvements required by REACH, both with respect to contents and communication could thus have a major impact on OHS management.…”
Section: Reach Impact On Occupational Risk Management Of Chemicalsmentioning
confidence: 99%
“…The failure of SDSs to communicate risk information to individuals with little knowledge of toxicology and chemistry has been noted in previous studies as well (Kolp et al ; Nicol et al ). The accuracy, comprehensibility, and use of MSDSs (the earlier version of the SDSs) were examined in a review article by Nicol and colleagues (). The study showed that many workers were unable to understand MSDSs due to the complex language used to describe hazards and the layouts of the MSDSs.…”
Section: Resultsmentioning
confidence: 77%
“…The obvious approach is therefore to use the hazard communication elements on the SDS of the assessed hazardous substance as primary information sources on hazardous properties for hazard banding. However, studies reveal that "accuracy and completeness were found to be relatively poor" on many SDSs (Nicol et al, 2008). Within the framework of the REACH regulation, the authorities are making efforts to improve the quality of SDSs.…”
Section: Discussionmentioning
confidence: 99%